Schematic rock paintings on granite in the province of Cáceres: the examples of the Cueva Larga del Pradillo and the Canchalejos de Belén (Trujillo) - Collado Giraldo, Hipólito; García Arranz, José Julio (Universidad de Salamanca, 2010)
An analysis is made of the representations belonging to two sites of schematic cave paintings located in a granitic area in the municipality of Trujillo (Cáceres): the Cueva Larga del Pradillo and the Canchalejos de Belén. Both sites are known of old, but only partially published, and one no longer exists. Reflections are made on the generic characteristics of these types of cave-art sites and their pictorial representations, on the state of cave-art investigations in Upper Extremadura, and on their chronological framework and socio-cultural context. El análisis de las representaciones pertenecientes a dos estaciones con pinturas rupestres esquemáticas localizadas en el berrocal del término municipal de Trujillo (Cáceres), la Cueva Larga del Pradillo y Los Canchalejos de Belén, ambas conocidas de antiguo pero parcialmente publicadas –y una de ellas desaparecida en la actualidad–, dan pie a unas reflexiones sobre las características genéricas de este tipo de yacimientos rupestres en soporte granítico y sus representaciones pictóricas, sobre el estado de la investigación en torno al mismo en la Alta Extremadura, y sobre su encuadre cronológico y contexto sociocultural.